2020
DOI: 10.15826/vestnik.2020.19.3.014
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Urbanization on Carbon Dioxide Emissions in the Regions of Russia

Abstract: Аннотация. В настоящее время в России, как и в других странах мира, существует проблема загрязнения окружающей среды, связанная с экономической деятельностью. Как известно, экономическое развитие происходит одновременно с процессами урбанизации. Целью нашего исследования является оценка влияния урбанизации на выбросы углекислого газа в регионах России. Исследование проводится для 77 российских регионов на основе данных Федеральной службы государственной статистики и Единой межведомственной информационно-статис… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Our results demonstrate a significant and positive impact of energy consumption on CO2 emissions in the GMM model. This result is also in line with the literature on Russia (Ketenci, 2018), and specifically on the Russian regions (Mariev et al, 2020;Sohag et al, 2021). This finding empha-sizes the necessity for energy efficiency, green energy (Grunewald, 2017), and eco-innovations in the energy sector.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results demonstrate a significant and positive impact of energy consumption on CO2 emissions in the GMM model. This result is also in line with the literature on Russia (Ketenci, 2018), and specifically on the Russian regions (Mariev et al, 2020;Sohag et al, 2021). This finding empha-sizes the necessity for energy efficiency, green energy (Grunewald, 2017), and eco-innovations in the energy sector.…”
Section: Discussionsupporting
confidence: 92%
“…At the regional level, economic growth, energy intensity, energy structure, industrialization, and urbanization are found to affect CO2 emissions in the provinces of China for the period 1990-2014, based on quantile regression method (Xu, 2016). There are articles on the regions of Russia devoted to the determinants of CO2 emissions that have confirmed the EKC hypothesis (Ivanova, 2019;Ketenci, 2018;Mariev et al, 2020). Moreover, researchers found that modern technologies decrease CO2 emissions and mitigate emissions from energy consumption, while environmental policy is effective in decreasing CO2 emissions (Sohag et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation